Ultrasound Artifacts – Part 2 - Bönhof, Jörg A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Part 2 discusses important artifacts in addition to those presented in part 1. Shadows and acoustic enhancement are based on regional differences in sound attenuation and are connected with the mode of action of depth gain compensation. They are not caused solely by the reflection properties of structures in terms of strong echoes → shadows, anechoic structure → acoustic enhancement. Anisotropy provides further evidence that echo strength is to be considered relative and is always linked to the equipment being used. Algorithms for "image improvement" can also result in artifacts as shown by black lines caused by image sharpening. Depending on the shape and position of the relevant structure, deviations from the assumed sound velocity result in incorrect positioning on the x-axis or refraction, which causes incorrect positioning on the y- and/or z-axis and may contribute significantly to shadows and acoustic enhancement.Nach den im Teil 1 vorgestellten Artefakten werden im Teil 2 weitere wichtige Artefakte erläutert. Schatten und Verstärkung beruhen auf regional unterschiedlicher Schallschwächung und sind mit der Wirkungsweise des Tiefenausgleichs verknüpft; also keineswegs nur den Reflexionseigenschaften von Strukturen im Sinne von starke Echos → Schatten, echofreies Gebilde → Verstärkung geschuldet. Anisotropie ist ein weiteres Beispiel dafür, dass Echostärke als relativ und nie losgelöst von der Gerätschaft zu betrachten ist. Auch Algorithmen zur „Bildverbesserung“ können zu Artefakten führen, wie sich am Beispiel von schwarzen Linien durch Bildschärfung zeigt. Abweichungen von der angenommenen Schallgeschwindigkeit ergeben je nach Form und Lage der verursachenden Struktur x-axiale Fehlplatzierungen oder Brechung, die zu y- und/oder z-axialen Fehlplatzierungen führt, sowie ggf. erheblich zu Schatten und Verstärkung beiträgt.